Influência das etapas do processo de abate de suínos na prevalência de patógenos e níveis de microrganismos indicadores de qualidade e higiene - Cê, Elton Rodrigo (2016)
The pig slaughter process involve different steps that can influence the microbiological quality of carcasses. At this, the understanding of the slaughter process on the microbiological aspects is necessary for the implementation and evaluation of critical control points. The microbiological control of the slaughter process should involve the evaluation of pathogens prevalence and levels of quality and hygiene indicator microorganisms. This study aimed at investigating the influence of steps slaughter process on the microbiological levels of pig carcasses, and evaluate if there is correlation between pathogens (Salmonella spp. and Listeria monocytogenes) and indicators (aerobic mesophilic counts, total coliforms, Escherichia coli and Enterobacteriaceae) microorganisms. A high Salmonella soroprevalence in pigs were founded before the slaughter (57.49 %). While the Salmonella prevalence in carcasses at the initial stage of the slaughter was 26.67 % and in the final stage 1.11 %, L. monocytogenes was detected only in the final washing and cooling steps, with a prevalence of 21.11 and 8.89 %, respectively. The aerobic mesophilic counts, Enterobacteriaceae, total coliforms and E. coli levels in initial steps of slaughter process were 4.25 ± 0.37; 1.25 ± 0.38; 1.10 ± 0.35 and 0.86 ± 0.36, respectively. At the end of slaughter process the results were lower (ranging from 0.16 at 2.70 log CFU/cm2). The step that most reduced microbiological levels was the scalding. The dehairing was a critical step that led to a significant increase of microorganisms levels in the process (p < 0.05). The evisceration not proved to be a critical step on the increase of microbial levels, differently of the final washing, which showed significant increases (p < 0.05) over the levels of aerobic counts, total coliforms, E. coli and enterobacterias (0.30; 0.36; 0.27 and 0.42 log respectively) and Salmonella spp. and L. monocytogenes. The chilling contributes significantly to the reduction of microbiological levels of carcasses, bringing them to levels below the all process stages, with the exception of scalding. No correlation between the hygiene indicator microorganisms used and presence of Salmonella spp. and L. monocytogenes were obtained (p < 0.05). The results show that steps in the process are critical to the sanitary profile, which implies the need to implement actions in the process to reducing the microbiological levels.